Optical density evaluation around the zirconia granules used as graft in rat calvaria - Farinazzo, Carolina Silva; Iwaki, Lilian Cristina Vessoni; Iwaki Filho, Liogi; Takeshita, Wilton Mitsunari; Silva, Mariliani Chicarelli da; Candido, Graciela Cristina (Acta Scientiarum. Health Sciences, 2014)
The aim of this study was to evaluate the optical density of the zirconia granules used as a graft in a rat calvarium model. Forty animals (Rattus Novergicus, albinus, Wistar) were divided into control and experimental groups and submitted to bone detects in the cranial cap using a trephine type burr 6 mmin diameter. The control group had the defect filled with blood coagulum, and the experimental group was filled with zirconia granules of 300 to 850 µm. The animals were sacrificed at intervals of 7, 14, 30, and 60 days. Digital images were obtained from the bone defect region, and optical density of the zirconia granules was measured using the Image Tool® 3.0. software (UTHSCSA,San Antonio, EUA). The histological analysis of the specimens was also evaluated. The values obtained were analyzed by statistical methods: Analysis of Variance, Welch’s Anova, and F Test. It was verified that the mean optical density of the bone repair process differs in all analyzed regions, irrespective of time (p < 0.0001). In the region with the zirconia graft, the mean density was always higher than the other regions analyzed, and the control group showed the same behavior of the experimental groups, but for the region with zirconia graft, the average density is always greater.